Two rare cases of sinonasal vascular malformation in the pediatric population. (November 2020) - Go, Beatrice; Poonia, Seerat K.; Devine, Conor; Javia, Luv; Buzi, Adva; Rizzi, Mark D.
Abstract: Vascular malformations presenting in the nasal cavity and paranasal sinuses are rare. Differentiating benign vascular malformations of the sinonasal cavity from other pathologic entities can be challenging and the role of preoperative angiography and embolization is not well defined. We present two unique cases of large pediatric sinonasal vascular malformations and describe their presentation, diagnosis and subsequent management. Both patients underwent embolization of the ipsilateral arterial supply followed by successful and complete endonasal surgical excision. This report provides description of management of the very rare occurrence of sinonasal vascular malformation in two adolescents.